2018
DOI: 10.1182/bloodadvances.2018016337
|View full text |Cite
|
Sign up to set email alerts
|

Structures of human plasma β–factor XIIa cocrystallized with potent inhibitors

Abstract: Activated factor XIIa (FXIIa) is a serine protease that has received a great deal of interest in recent years as a potential target for the development of new antithrombotics. Despite the strong interest in obtaining structural information, only the structure of the FXIIa catalytic domain in its zymogen conformation is available. In this work, reproducible experimental conditions found for the crystallization of human plasma β-FXIIa and crystal growth optimization have led to determination of the first structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 37 publications
2
72
0
Order By: Relevance
“…The energy contributions of the respective active site residues toward the binding and stabilization of BEN were further quantified using the MM/PBSA-integrated per-residue decomposition analysis and presented in Figure 10. Taken together, complementary interactions of BEN with these active site residues could account for the high-affinity binding, stability, and inhibitory activity reportedly exhibited by BEN toward FXIIa according to previous reports (Dementiev et al, 2018). Moreover, estimations of the free binding energy revealed that BEN exhibited a favorable binding toward a FXIIa with a ΔG value of −16.64 kcal/mol and a considerably high electrostatic energy of −11.72 kcal/mol as shown in Table 1, indicative of the occurrence of favorable interactions in agreement with results earlier discussed.…”
Section: Differential Binding Analysis Of the Binding Of Benzamidinesupporting
confidence: 78%
See 3 more Smart Citations
“…The energy contributions of the respective active site residues toward the binding and stabilization of BEN were further quantified using the MM/PBSA-integrated per-residue decomposition analysis and presented in Figure 10. Taken together, complementary interactions of BEN with these active site residues could account for the high-affinity binding, stability, and inhibitory activity reportedly exhibited by BEN toward FXIIa according to previous reports (Dementiev et al, 2018). Moreover, estimations of the free binding energy revealed that BEN exhibited a favorable binding toward a FXIIa with a ΔG value of −16.64 kcal/mol and a considerably high electrostatic energy of −11.72 kcal/mol as shown in Table 1, indicative of the occurrence of favorable interactions in agreement with results earlier discussed.…”
Section: Differential Binding Analysis Of the Binding Of Benzamidinesupporting
confidence: 78%
“…The lowering of the Cα atomistic motions of these loops and residues could possibly be attributed to the restraint effects imposed by the complementary interactions with BEN. This is in contrast to the unbound system that exhibited a considerable motion in its catalytic loops, a feature which facilitates the activation of protease enzymes activation (Dementiev et al., ). The binding of BEN also resulted in an increase in average structural flexibility of the binding pocket residues as showcased by the root‐mean‐square fluctuation (RMSF) analysis shown in Figure .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…By contrast, deficiency of either FXII or FXI protects against thrombosis in murine models . Despite the importance of these proteins in thrombosis, full‐length crystal structures are only available for the zymogen FXI and β ‐FXIIa , a product of activation by PKa .…”
Section: Introductionmentioning
confidence: 99%